Himno Patriotico al 15 de setiembre: un canto de libertad - Carvajal, Maria Isabel (2013)
The musical heritage of Costa Rica has many anthems and musical scores which make reference to historic events in the country’s History. With the exception of the studies done on the National Anthem of Costa Rica, there is no research pertaining other musical scores from that genre. Therefore, this work will investigate the circumstances that gave rise to the Patriotic Anthem for September 15th. On this article, I will present some of the findings on the subject.